Mesenchymal Stem Cells and Tissue Bioengineering Applications in Sheep as Ideal Model - Talita D’Paula Tavares Pereira Muniz; Mariana Correa Rossi; Vânia Maria de Vasconcelos Machado; Ana Liz Garcia Alves (Stem Cells International)
The most common technologies in tissue engineering include growth factor therapies; metal implants, such as titanium; 3D bioprinting; nanoimprinting for ceramic/polymer scaffolds; and cell therapies, such as mesenchymal stem cells (MSCs). Cell therapy is a promising alternative to organ grafts and transplants in the treatment of numerous musculoskeletal diseases. MSCs have increasingly been used in generative medicine due to their specialized self-renewal, immunomodulation, multiplication, and differentiation properties. To further expand the potential of these cells in tissue repair, significant efforts are currently dedicated to the production of biomaterials with desirable short- and long-term biophysical properties that can aid the differentiation and expansion of MSCs. Biomaterials support MSC differentiation by modulating their characteristics, such as composition, mechanical properties, porosity, and topography. This review aimed to describe recent MSC approaches, including those associated with biomaterials, from experimental, clinical, and preclinical studies with sheep models.